Textile antenna array for bio-radar applications - Gouveia, Carolina (2021)
In this paper, a 2 x 2 antenna array operating at 5.8 GHz is presented for vital signs acquisition using a radar-based system, also known as bio-radar. Since these non-contact systems have multiple applications, their front-end design should take into account the monitoring environment of each specific application. In this sense, the antenna design has a crucial role to guarantee the proper integration of the full system, considering different materials. In this work, the antennas were made using textile materials, in order to integrate the bio-radar system in a car seat cover. This work presents the design of the antenna and the results achieved through measures in the anechoic chamber. Furthermore, respiratory signals were also acquired with the manufactured antennas and they are herein presented for validation purposes.